STRATEGI PEMBELJARAN INKUIRI (SPI) TENTANG KARTU INTEGRAL DAPAT MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DAN MEMBUAT SISWA SENANG DALAM BELAJAR MATEMATIKA DI KELAS XII MIA MADRASAH ALIYAH NEGERI BINJAI SEMESTER GANJIL TAHUN PELAJARAN 2022 / 2023 - Siti Rohani (Jurnal Guru Kita PGSD, 2023)
Inquiry Learning Strategies (Spi) About Integral Cards Can Improve Students' Mathematics Learning Outcomes and Make Students Enjoy Learning Mathematics in Class Xii Mia Madrasah Aliyah Negeri Binjai Odd Semester 2022 / 2023 Academic Year. One of the innovations in learning mathematics carried out by mathematics teachers is trying to use the Inquiry Learning Strategy (SPI) about Integral material as outlined in the Integral card game with the aim of being able to improve students' mathematics learning outcomes and make students happy in learning mathematics especially in class XII MIA Madrasah Aliyah Negeri Binjai Odd Semester 2022 / 2023 Academic Year. The results can be seen from the average daily value of students' mathematics after conducting research using Inquiry Learning Strategies (SPI), namely the initial activity of 87.33 increased to 90.42 in the first cycle and increased to 91.28 increased to 92.97 in the second cycle. And the results of the mathematics teacher's interview with students that learning mathematics is fun and not boring if learning mathematics is accompanied by playing (Integral material made into Integral card shapes).